Evaluation of the efficacy of a topical slimming and anti-cellulite cream containing caffeine in vivo study - Mohamad, Nor Hakimah; Ab. Hadi, Hazrina; Doolaanea, Abd Almonem (2018)
INTRODUCTION: Cellulite or lipodystrophy is a major aesthetical concern among women who want to look beautiful. OBJECTIVES: The aim of this study was to evaluate the effectiveness of a topical slimming and anti-cellulite cream containing caffeine on treatment of cellulite and other various skin parameters on human volunteers. METHODS: Placebo and formulation containing 2.5% of caffeine were prepared and applied to the upper arm and abdomen of 24 healthy volunteers, twice daily in order to determine the efficacy of the formulation as anti-cellulite and slimming agent for 12 weeks. The hydration, elasticity, trans-epidermal water loss (TEWL), body fat content and circumference measurement of abdomen and upper arm of volunteers were evaluated and monitored at baseline (before application of creams), 2nd, 4th, 8th and 12th weeks of study period to measure the effect produced by the creams. RESULTS: The significant (p<0.05) reduction of fat content of upper arm and abdomen was observed after 4 weeks. The circumference measurement of upper arm was reduced significantly (p<0.05) after 8 weeks application of formulation while circumference measurement of abdomen was reduced after 12 weeks. The TEWL of abdomen values showed a significant (p<0.05) decreased immediately after 2 week of application while the TEWL of arm was reduced significantly (p<0.05) after 4 week. Skin hydration was significantly (p<0.05) increased by both creams immediately after 2 week of application. However, there was no changes was observed in skin elasticity for both creams over 12 week period study. CONCLUSION: The formulation containing caffeine was able to improve sign of cellulite, reduced circumference measurement, fat content and TEWL as well increased hydration of skin.